1998
DOI: 10.1152/ajpgi.1998.274.1.g103
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide metabolism by gastric glands and H+-K+-ATPase-enriched membranes

Abstract: α-Toxin-permeabilized gastric glands represent a functional model in which acid secretion can be elicited by either adenosine 3′,5′-cyclic monophosphate (cAMP) or ATP, with proven morphological and functional transition between resting and secretory states [X. Yao, S. M. Karam, M. Ramilo, Q. Rong, A. Thibodeau, and J. G. Forte. Am. J. Physiol. 271 ( Cell Physiol. 40): C61–C73, 1996.] In this study we use α-toxin-permeabilized rabbit gastric glands to study energy metabolism and the interplay between nucleotide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 39 publications
(59 reference statements)
2
10
0
Order By: Relevance
“…In addition, 1 mM of either AMP or ADP could substitute for 1 mM ATP in stimulation of AP accumulation by the SLO-permeabilized glands (data not shown). These data are very much like those obtained with ␣-toxinpermeabilized glands, in which it was shown that any adenine nucleotide source could provide the necessary energy intermediate (19). Even cAMP serves both as a second messenger to trigger PKA activation and a suitable source of ATP, through conversion to AMP by phosphodiesterase and subsequent resynthesis to ATP.…”
Section: Resultssupporting
confidence: 76%
See 4 more Smart Citations
“…In addition, 1 mM of either AMP or ADP could substitute for 1 mM ATP in stimulation of AP accumulation by the SLO-permeabilized glands (data not shown). These data are very much like those obtained with ␣-toxinpermeabilized glands, in which it was shown that any adenine nucleotide source could provide the necessary energy intermediate (19). Even cAMP serves both as a second messenger to trigger PKA activation and a suitable source of ATP, through conversion to AMP by phosphodiesterase and subsequent resynthesis to ATP.…”
Section: Resultssupporting
confidence: 76%
“…Direct stimulation of the protein kinase A (PKA) pathway in intact glands with DBcAMP and IBMX resulted in an 11.7-fold increase in AP ratio over resting glands (233.7 Ϯ 24.7 and 19.9 Ϯ 5.1, respectively). As with other permeabilized gland models (1,10,15,19,22), acid accumulation in SLO-treated glands requires substrates for oxidative phosphorylation to regenerate ATP required by the gastric proton pump. SLO-permeabilized glands incubated with ATP and cAMP but lacking pyruvate and succinate showed no significant increase in AP ratio (7.4 Ϯ 0.4) compared with those without the nucleotides (8.7 Ϯ 0.6).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations